DETECTION OF NEWCASTLE DISEASE VIRUS BY NESTED REVERSE TRANSCRIPTASE-POLYMERASE CHAIN REACTION - Ayu Mirah Adi, Anak Agung; Mantik Astawa, Nyoman; Santhia Adhy Putra, Ketut; Matsumoto, Yasunobu (Jurnal Veteriner; Vol 9 No 3 (2008), 2008)
A study to utilize nested reverse trancriptase-polymerase chain reaction (RT-PCR) for the detection ofNewcastle disease virus (NDV) infection was carried out. NDV isolated from an outbreak in KarangasemDistrict of Bali, Indonesia was propagated in chicken embryos and its pathogenicity was determined byinoculation in 3 week-old chickens. Organ samples were collected from infected chickens for nested-RTPCR.Out of several different pairs of primers designed for study, 3 pairs of primers (F4s-F6r/F5s-F5r,F8s-F10r/F8s-F8r and F12s-F14s/F13s-F13r), each of which for first-round/nested PCR, was able to amplifyspecific regions of NDV genome. In the fist-round PCR, the PCR product of 1500 bps was not clearly visiblein the agarose gel following electrophoresis. In nested PCR a PCR product of 500 bp was clearly visible onagarose gel following electrophoresis. The 3 pairs of primers appeared to be potential for an accurate andrapid detection NDV in the infected host.
Keywords: Newcastle disease virus reverse transcriptase, polymerase chain reaction